Genetic variation in IL-1β, IL-2, IL-6, TSPO and BDNF and response to duloxetine or placebo treatment in major depressive disorder. (November 2015) - Maciukiewicz, Malgorzata; Marshe, Victoria S; Tiwari, Arun K; Fonseka, Trehani M; Freeman, Natalie; Rotzinger, Susan; Foster, Jane A; Kennedy, James L; Kennedy, Sidney H; Müller, Daniel J
Aim: This study investigated polymorphisms of five inflammatory-related genes for association with duloxetine and placebo response in patients with major depression.Patients & methods: Twenty SNPs in IL-1β, IL-2, IL-6, TSPO and BDNF were genotyped in major depressive disorder patients treated with either duloxetine (n = 215) or placebo (n = 235) for up to 8 weeks. Treatment response was measured with the Montgomery–Åsberg Depression Rating Scale.Results: IL-6 variants rs2066992 and rs10242595 were nominally associated with response to duloxetine (p = 0.047 and p = 0.028, respectively). Notably, the variant rs2066992 was also associated with placebo response (p = 0.026). However, none of our results remained significant after correction for multiple testing.Conclusion: Our findings tentatively suggest that IL-6 variants play a role in duloxetine and placebo response, which warrants further investigation.